Nitrogen and Phosphorus pollution mitigation through down-scaling cattle production in Germany - Karen Arcia; Stephan von Cramon-Taubadel (Georg-August University of Göttingen, RTG 2654 Sustainable Food Systems, 2024)
Reactive nitrogen (N) and phosphorus (P) pollution in Germany is mainly caused by production of cattle meat and milk, which is mostly consumed domestically. This pollution comes at a high external costs not yet addressed by current policies. We explore scenarios where reduced domestic cattle production aims to lower N and P pollution. We also analyze the potential effects of two policy measures, cattle buy-outs and input taxation, on reducing production. The research discusses the need to decrease cattle milk and meat consumption alongside cattle production reduction to ensure that negative environmental effects such as N and P pollution are not merely shifted to other production regions. Further research should examine the policies under consequential computational economic framework toward precise magnitude of effects.
Keywords: Q52; Q53; Q18; H23; 330; Nutrient pollution mitigation; Policy measures; Buyout; Taxation; Grassland utilization; Nutrient cycles